Preserved critical ability and free will in deep hypnosis during oral surgery. Issue 3 (18th January 2021) - Facco, Enrico; Bacci, Christian; Casiglia, Edoardo; Zanette, Gastone
ABSTRACT: Free will is a complex construct that includes critical reasoning, sense of ownership, and agency. The whole history of hypnosis has been linked to suggestibility. Little agreement has been reached, however, on exactly what we mean by suggestibility, and its role in hypnosis, despite the abundance of studies, hypotheses, and theories published to date. We report on a highly hypnotizable patient with a previous allergy to lidocaine and paradoxical reactions to pharmacological sedation, who underwent oral surgery with mepivacaine for local anesthesia, and hypnosis for sedation. During the procedure, she felt some pain and the hypnotist recommended bupivacaine to ensure lasting anesthesia. While remaining under deep hypnosis, the patient refused to change anesthetic and decided autonomously to continue with mepivacaine (for which she had previously been tested for allergy). Our case clearly shows a preserved, exemplary reasoning and ability to make autonomous decisions diverging from the hypnotist's advice while under deep hypnosis.